Fuzzy Multiple Attribute Decision Making Menggunakan TOPSIS Pada Sistem Pendukung Keputusan Pemilihan Wireless Router - Rini Nuraini; Yeni Daniarti; Irsyad Purbha Irwansyah; Alfry Aristo J Sinlae; Setiawansyah Setiawansyah (JURIKOM (Jurnal Riset Komputer), 2022)
Selection of the right wireless router can maximize the performance of the internet network. Especially for a company whose business is very dependent on the internet network, choosing the right wireless router is an important factor. The purpose of this study is to implement one of the Fuzzy Multiple Attribute Decision Making (FMADM) approaches, namely the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method in a decision support system for selecting wireless router devices to help individuals and companies determine the right wireless router and according to what the user wants. The TOPSIS method is used because it is practical in its use, and has simplicity in concept, efficiency in the computational process and the best alternative is obtained by paying attention to the distance of the closest positive ideal solution and the farthest negative ideal solution distance. The system is built with software development techniques using the Extreme Programming (XP) method which begins with the planning, design, coding and testing stages. The developed system has functions such as being able to manage alternative data, criteria data, weight data, alternative values for each criterion, perform calculations using the TOPSIS method and can display the best alternative results. The results of the black-box testing show that the developed system can function and run well. In addition, the results by calculating manually with the system show the same results.